An Evaluation of Flexible Workday Policies in Job Shops - Yang, Kum Khiong (Institutional Knowledge at Singapore Management University, 2002)
Job shops have long faced pressures for improvements in a challenging and volatile environment. Today's trends of global competition and shortening of product life cycles suggest that both the challenges and the intensity of market volatility will only increase. Consequently, the study of tactics for maximizing the flexibility and responsiveness of a job shop is important. Indeed, there is a significant body of literature that has produced guidelines on when and how to deploy tactics such as alternate routings for jobs and transfers on cross-trained workers between machines. In this paper we consider a different tactic by adjusting the length of workdays. Hours in excess of a 40-hour week are exchanged for compensatory time off at time and a half, and the total amount of accrued compensatory time is limited to no more than 160 hours in accordance with pending legislation. We propose several simple flexible workday policies that are based on an input/output control approach and investigate their performance in a simulated job shop. We find significant gains in performance over a fixed schedule of eight hours per day. Our results also provide insights into the selection of policy parameters. [ABSTRACT FROM AUTHOR]